THE INFLUENCE OF COMPANY SIZE, PUBLIC ACCOUNTING FIRM SIZE, AND PROFITABILITY ON AUDIT REPORT LAG - Susanti, Lena; Sigit Mareta (Fakultas Bisnis dan Ilmu Sosial Universitas Dian Nusantara, 2024)
This research aims to investigate company size, KAP size, and profitability on Audit Report Lag. The research sample is derived from 74 companies in the Basic and Chemical Sector listed on the Indonesia Stock Exchange (BEI) during the period from 2019 to 2022. The study investigates the influence of company size, KAP size, and profitability on Audit Report Lag. The research methodology employed is quantitative research using SPSS version 26, 2019. The research type used is causal research, aimed at testing hypotheses regarding the influence of one or more independent variables on another dependent variable. The research findings state that Company Size, Audit Firm Size, and Profitability do not significantly impact the Audit Report Delay in companies within the Basic and Chemical Industry sector listed on the Indonesia Stock Exchange From 2019 to 2023.